Pengaruh Dance Movement Therapy terhadap Perubahan Tekanan Darah pada Lansia Hipertensi - Supriadin Supriadin; Agung Waluyo; Rohman Azzam (Journal of Telenursing (JOTING), 2019)
This study aims to determine the effect of dance movement therapy on changes in blood pressure in hypertensive elderly. The research design used a quasi-experimental pre-post control group. The results showed a significant difference in changes in systolic and diastolic blood pressure after being given dance movement therapy (t = 2.781, p = 0.013), t = 2.465, p = 0.025), as well as changes in systolic and diastolic blood pressure after the intervention at control group (t = 1.458, p = 0.163), t = 0.606, p = 0.552). In conclusion, dance movement therapy can significantly reduce systolic blood pressure in hypertensive patients. Keywords: Dance Movement Therapy, Primary Hypertension, Blood Pressure